Uso da água cinza tratada na produção do capim tanzânia no semiárido brasileiro - Medeiros, Igor Estevão Souza (Universidade Federal Rural do Semi-Árido, 2017)
The present work aimed to analyze the viability of the use of gray water for Tanzania grass production. The experiment was conducted in a greenhouse at the Federal Rural Semiarid University, Mossoró-RN. The gray water used came from a residence located in the settlement P. Monte Alegre I, in the municipality of Upanema-RN. For the treatment and agricultural use of gray water, a system was set up consisting of an inspection box, septic tank, organic filter and reservoir. The experimental design was a randomized block with six replicates and six treatments, totaling 36 plots. The experiment was conducted in pots with 40L capacity, containing four plants per pot. The treatments were constituted by water supply (AA), treated gray water (ACT), and distributed as follows: Treatment 1: 100% AA and 0% ACT; Treatment 2: 75% AA and 25% ACT; Treatment 3: 50% AA and 50% ACT; Treatment 4: 25% AA and 75% ACT; Treatment 5: 0% AA and 100% ACT, and Treatment 6: 100% AA and bovine manure tanned at the rate of 10%. During the experimental period, the physical-chemical characteristics (pH, EC, SS, SD, Na, Mg, Ca, Fe, Mn, Zn, Cu, Pb, Ni and Cd) and microbiological (thermotolerant coliforms) Of the effluent collected at different points in the treatment system. After each cut, the agronomic parameters (number of leaves, height of the plants, biomass production and leaf area) were analyzed. The results indicated that the T6 treatment had values of leaf number and leaf area superior to the other treatments, in the first and second cuts. In the third cut, the highest values of leaf number and leaf area were observed in T5. Regarding productivity, there was no significant difference between T6 treatments. T3, T4 and T5, in the third cut. However, T1 treatment provided the lowest productivity
Monografia
Keywords: Efluente; Reúso; Forragem; Biomassa; Effluent; Reuse; Reuse; Biomass; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA